2015
DOI: 10.1055/s-0035-1559767
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolically Healthy Obese and Metabolically Obese but Normal Weight in Adults Worldwide: A Meta-Analysis

Abstract: The objective of the present study was to summarize the prevalence and influencing factors of metabolically healthy obese (MHO) and metabolically obese but normal weight (MONW) among people ≥ 18 years old in the general population worldwide. We searched for studies of the prevalence of MHO and MONW published in English and Chinese up to October 2013. Pooled prevalence estimates were calculated by a random-effects model according to a Q test. The effects of gender, region, age, sample size, smoking, and alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 23 publications
(27 reference statements)
7
83
1
9
Order By: Relevance
“…The prevalence of MHO in Europe varied from 1.1 to 6.6% and that of MUO from 7.2 to 21.4% [32, 39-41]. Compared to a European population, Americans had a higher prevalence of MHO, and this was consistent with a meta-analysis [42] focusing on the prevalence of MHO in adults. Studies in Korea showed that the prevalence of MHO varied from 5.7 to 25.8% and the prevalence of MUO from 13.6 to 25.9%, and most studies used ATPIII to define metabolic abnormality [22, 29, 43-45].…”
Section: Discussionsupporting
confidence: 76%
“…The prevalence of MHO in Europe varied from 1.1 to 6.6% and that of MUO from 7.2 to 21.4% [32, 39-41]. Compared to a European population, Americans had a higher prevalence of MHO, and this was consistent with a meta-analysis [42] focusing on the prevalence of MHO in adults. Studies in Korea showed that the prevalence of MHO varied from 5.7 to 25.8% and the prevalence of MUO from 13.6 to 25.9%, and most studies used ATPIII to define metabolic abnormality [22, 29, 43-45].…”
Section: Discussionsupporting
confidence: 76%
“…Although, actual weight gain has been found ranging from 1.6 lbs (0.73 kg) to 8.8 lbs (3.99 kg), some studies have even found that no significant weight gain occurs in the first year of college (6)(7)(8). The abnormal weight gain and obesity has been reported as an epidemic phenomenon according to the world health organization (WHO), with an approximate number of 1.4 billion worldwide overweight and 300 million persons clinically obese (9,10). Governments and health organizations are trying to do the necessary strategies to prevent the negative consequences of obesity such as cardiac, endocrine and cancer diseases (11).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolically unhealthy phenotype is defined by two or more of four of these components except for waist circumference, and the metabolic syndrome is identified by the presence of three or more of five components (911). A recent world-wide meta-analysis shows that 30.0% (95% CI: 25.6–35.6%) of normal-weight adults were metabolically unhealthy (12). Using criteria of two or more metabolic abnormalities, Wildman et al found that 23.5% of normal-weight US adults were metabolically unhealthy (13).…”
Section: Introductionmentioning
confidence: 99%